A prospective interventional study on efficacy of fractional carbon dioxide laser in primary cutaneous macular amyloidosis - Roshany Sakthibalan; Brinda G David; Roshni Menon (Pigment International)
Background: Macular amyloidosis (MA) represents a common variant of primary localized cutaneous amyloidosis (PLCA). Many therapeutic modalities, including topical and systemic medications, phototherapy, photochemotherapy, dermabrasion, and lasers have been suggested for PLCA with variable efficacy. Over the past decade, several studies have reported successful treatment of PLCA with different types of lasers. Aim: To evaluate the efficacy and safety profile of fractional carbon dioxide laser (FrCO2) in primary cutaneous MA. Methods: Using the consecutive sampling technique, 30 clinically confirmed cases of MA aged 18 years and above attending the dermatology out-patient department were recruited for a prospective, single group, interventional study. Each patient received three sessions with 4 weeks interval and then subsequently monitored for 20 weeks. The degree of pigmentation, rippling, itching, overall progress, and patient satisfaction were graded and compared for each patient. SPSS software version 23.0 was used for data analysis. Results: There was a statistically significant (P < 0.001) improvement in the mean percentage of the degree of pigmentation, itching (P < 0.001), and rippling scores (P = 0.03). Marked patient satisfaction was noted at 20 weeks. The excellent safety profile was noted. Conclusion: Our study has shown a positive response to treating MA with FrCO2 laser. Patients were highly satisfied, as there was a significant reduction in itching, pigmentation, and area of the skin lesion with no significant side effects. Our study points towards better efficacy of FrCO2 laser in MA with a good safety profile and better patient satisfaction.